1991
DOI: 10.1002/art.1780341007
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte Adhesion to Human Synovial Fibroblasts. Role of Cytokines and the Interaction Between Intercellular Adhesion Molecule 1 and CD11a/CD18

Abstract: We studied the adhesion of human peripheral blood T lymphocytes to human synovial fibroblasts stimulated with interferon-y (IFNy), tumor necrosis factor a (TNFcu), interleukin-lp (IL-lp), or combinations of these cytokines. T lymphocytes bound poorly to untreated human synovial fibroblasts. IFN y treatment resulted id the largest increase in adhesion, followed by TNFa and IL-1p. Combinations of IFNy + TNFa and IFNy + I L -l p had a synergistic effect on intercellular adhesion molecule 1 (ICAM-1) expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…In vitro studies revealed that human T cells have the ability to adhere to synoviocytes as well as to dermal fibroblasts via CD2/CD58 (LFA-3) and LFA-1 (CD11a/CD18)/CD54 (ICAM-1) interactions (12,13,49). Furthermore, the cellular adhesion between T cells and synoviocytes induces the production of IL-1␤ by synovial cells in part through LFA-1-ICAM-1 interaction (17).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies revealed that human T cells have the ability to adhere to synoviocytes as well as to dermal fibroblasts via CD2/CD58 (LFA-3) and LFA-1 (CD11a/CD18)/CD54 (ICAM-1) interactions (12,13,49). Furthermore, the cellular adhesion between T cells and synoviocytes induces the production of IL-1␤ by synovial cells in part through LFA-1-ICAM-1 interaction (17).…”
Section: Discussionmentioning
confidence: 99%
“…The integrin CD11a/CD18 (LFA-1) clusters at the contact point between T cell and FLS (8) and T cell adherence to FLS is inhibited by blocking Ab to LFA-1 (9). FLS also express significant MHC class II in vivo (10), which can be reinduced in vitro (11,12).…”
Section: Interactions Of T Cells With Fibroblast-like Synoviocytesmentioning
confidence: 99%
“…Although other authors reported the induction of periapical lesion by allowing pulp exposure of rat molars 7,8) , studies on laboratory animals using m-CT over time are very few 5) . In conventional R_mCT, the x-ray tube and sensor are fixed therefore the image is difficult to aim since the tail and head would contact the tube while rotating in vivo, which is essential in sample preparation.…”
Section: Discussionmentioning
confidence: 99%